ANALISIS FAKTOR KURANGNYA MINAT DAN MOTIVASI SISWA SMA ASISI DALAM MEMPELAJARI BAHASA MANDARIN - Apriadi, Apriadi; Thamrin, Lily; Afrimonika, Yoanna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Mandarin is one of the languages in the world that difficult to learn. Therefore, interest and motivation learning needed to encourage students to be interested learning Mandarin. The factors of interest and motivation learning each have internal and external factors. Internal factors of interest in learning include: hopping, attention, and enjoyment. External factors include: school environment, social environment, and family. Internal factors of learning motivation include: interest and initiative. External factors include: achievement value, utility value, and teachers. The author conducted research at Santo Fransiskus Assisi High School, especially grade 11 students, to examine how the learning process takes place and what factors influence students' disinterest and motivation in learning Mandarin. The author uses questionnaire, interview and observation research methods. With the aim of researching the conditions in which learning takes place and finding out between the factors of interest and motivation to learn, what factors most influence grade 11 students who are not interested and not motivated in learning Mandarin. The research results showed that during observations of learning process, interaction between teachers and students was very lacking and teachers used teaching methods that did not attract students' interestin learning. And also the research results show that the factor that most influences the disengagement of grade 11 students at Santo Fransiskus Assisi High School learning Mandarin is "school environment" factor with a percentage of 33.15%. Meanwhile, the factor that influencesstudents' lack of motivation learning is "achievement value" factor with a percentage of 26.44%.